What’s under the hood? Phylogeny and taxonomy of the snake genera Parasuta Worrell and Suta Worrell (Squamata: Elapidae), with a description of a new species from the Pilbara, Western Australia - Maryan, Brad; Brennan, Ian G.; Hutchinson, Mark N.; Geidans, Lukas S. (Zootaxa, 2020)
Despite decades of phylogenetic studies, the generic and species-level relationships of some Australian elapid snakes remain problematic. The morphologically conservative genus Parasuta comprises small nocturnal snakes with a particularly obfuscated taxonomic history. Here we provide a molecular phylogenetic analysis of all currently recognised species including members of the sister genus Suta and provide new morphological data that lead to a taxonomic revision of generic and species boundaries. We failed to find support for monophyly of Parasuta or Suta, instead supporting previous evidence that these two genera should be combined. Our species-level investigations revise the boundaries between P. gouldii (Gray) and P. spectabilis (Krefft) resulting in recognition that both P. spectabilis bushi (Storr) and P. spectabilis nullarbor (Storr) are conspecific with P. gouldii. We also find the Pilbara population of P. monachus (Storr) to be specifically distinct. As a consequence of this information, we synonymise Parasuta with its senior synonym Suta, redescribe S. gouldii, S. monachus and S. spectabilis to clarify morphological and geographical boundaries and describe S. gaikhorstorum sp. nov., which differs from all other described Suta species, including the geographically proximate and similar-looking S. monachus, by a combination of molecular genetic markers, morphometric attributes, details of colouration and scalation. The recognition of S. gaikhorstorum sp. nov. adds to the growing list of the many endemic reptiles from this exceptionally diverse biotic region. We also designate a lectotype for S. spectabilis from the original syntype series, highlight a distinctive population from the Great Victoria Desert in Western Australia and comment on further unresolved issues regarding the relationships between S. dwyeri (Worrell) and S. nigriceps (Gȕnther).